2021
DOI: 10.24815/jpsi.v9i4.21416
|View full text |Cite
|
Sign up to set email alerts
|

Discovering the Views of Indonesian Students’ Responses to Use the Booklet During the Covid-19 Pandemic Situation

Abstract: The Covid-19 situations impacted the teaching and learning which reducing our activities by using the online platforms. The booklet is one of the solutions to use during a covid-19 situation which provides the opportunity to improve the learning process. This study aims to discover students’ responses to use the booklet as learning media which contains the results of an inventory of medicinal plants in the biology courses. The questionnaire sheet was used as the instrument which contains the affective, cogniti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 34 publications
0
1
0
Order By: Relevance
“…Similar to Lendra and Marlenywati [20], they confirmed that the education media was increased adolescent knowledge from 11.70 to 16.23% after intervention (p=0.000). The study stated that there are two indicators to improve students' perceptions of the information presented and students' perceptions of the knowledge obtained from the information presented [21]. Adolescent is an proper group for receiving education and promotion using attractive media that can increase message absorption, generate interest in learning, and be easy to understand [22].…”
Section: The Difference Of Knowledge and Macronutrient Intake Before ...mentioning
confidence: 99%
“…Similar to Lendra and Marlenywati [20], they confirmed that the education media was increased adolescent knowledge from 11.70 to 16.23% after intervention (p=0.000). The study stated that there are two indicators to improve students' perceptions of the information presented and students' perceptions of the knowledge obtained from the information presented [21]. Adolescent is an proper group for receiving education and promotion using attractive media that can increase message absorption, generate interest in learning, and be easy to understand [22].…”
Section: The Difference Of Knowledge and Macronutrient Intake Before ...mentioning
confidence: 99%